2019
DOI: 10.1370/afm.2419
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Case Management in Primary Care Associated With Positive Outcomes for Frequent Users of Health Care: A Systematic Review

Abstract: PURPOSE Case management (CM) interventions are effective for frequent users of health care services, but little is known about which intervention characteristics lead to positive outcomes. We sought to identify characteristics of CM that yield positive outcomes among frequent users with chronic disease in primary care. METHODS For this systematic review of both quantitative and qualitative studies, we searched MEDLINE, CINAHL, Embase, and PsycINFO (1996 to September 2017) and included articles meeting the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
1
18

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 64 publications
0
64
1
18
Order By: Relevance
“…To promote their engagement, all team members were invited to 2 working sessions, during which we focused the scope of the RS. Specifically, the review team identified the research question, clarified the purpose of the review, and articulated an initial program theory based on the findings of the parent systematic review 26 and other CM literature. The initial program theory consisted of the following 5 main resources: case finding, care planning, coordination/ integration of services, self-management support, and…”
Section: Stage 1 Focusing the Scope Of The Realist Synthesis And Promentioning
confidence: 99%
See 3 more Smart Citations
“…To promote their engagement, all team members were invited to 2 working sessions, during which we focused the scope of the RS. Specifically, the review team identified the research question, clarified the purpose of the review, and articulated an initial program theory based on the findings of the parent systematic review 26 and other CM literature. The initial program theory consisted of the following 5 main resources: case finding, care planning, coordination/ integration of services, self-management support, and…”
Section: Stage 1 Focusing the Scope Of The Realist Synthesis And Promentioning
confidence: 99%
“…As planned in our protocol, 25 we searched for evidence from all of the studies included in our parent systematic review detailing the methods and characteristics of the included studies. 26 The comprehensive search strategy used in our parent systematic review yielded 21 peer-reviewed articles published during the period 1996 to September 2017 and evaluating 19 interventions in primary care settings designed to improve care among adult frequent users of health care services who were affected by at least 1 chronic physical condition. In accordance with RS methodology supporting the inclusion of data from various sources, we used a cluster search to identify additional documents relevant to each CM intervention.…”
Section: Stage 2 Searching For Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, the appropriate answers to their needs, and consequently reducing the visits to ED and ambulance transports may be achieved. These solutions range from case management [4][5][6] to individual care plans, [7][8][9] and facilitated contacts with healthcare providers. 10 However, to be able to offer and consider such a form of advance care planning for apparently frail patients, they first need to be identified.…”
Section: Introductionmentioning
confidence: 99%